Zen and the Art of Everyday Evaluation - Michael Scriven (The Evaluation Center at Western Michigan University, 2004)
The article draws a parallel between Zen Buddhism's aims and evaluation's goals of extending everyday reasoning into science. It announces an essay competition around the question of what values to use when evaluating revolutions. A humorous section points readers to the Journal of Nondestructive Evaluation.